Optimasi Variasi Jumlah Blade Inlet Turbo Pada Waterjet Thruster Mini Produk 3D Printing Dengan Filamen ST PLA Terhadap Gaya Dorong Menggunakan Metode Taguchi - Thala Viniolita; Hasdiansah, Hasdiansah; Suzen, Zaldy S (Politeknik Manufaktur Negeri Bangka Belitung, 2024)
The needs of fishermen in increasing fish catches are driven by the propulsion system in shipping. A ship’s speed is influenced by the drive system used. The ship’s propulsion system is the propeller. This research aims to determine the factors of research that affect the results of thrust at the level of research that has been printed using an Ender 3 Pro 3D printing machine. In this research, the Taguchi method is used in printing and as an experimental design that will be carried out. The research variables to be carried out are the number of blades inlet turbo, impeller type, and the number of blades outlet turbo on the mini waterjet thruster prototype. In this research produced the highest thrust force in experiment number 8 with a value of 2,330 Nusing blade inlet turbo 8, impeller type 2, and using blade outlet turbo 6. As for the lowest thrust force in experiment number 3 with a value of 1,251 N using blade inlet turbo 6, impeller type 3, and using blade outlet turbo 8. So based on the results of the research conducted it can be concluded that the selection of research factors affects the results of the thrust force.